Expression and Characterization of i-Photina as an Efficient Photoprotein - Fatemeh Ahmadi; Reza H. Sajedi; Mehdi Zeinoddini (Iranian South Medical Journal, 2015)
Background: Nowadays photoproteins are excellent reporter systems as they have virtually no background. The most commonly studied photoprotein is aequorin. But because of it’s low quantum yield and very fast reaction kinetic this photoprotein assay don’t adapt for High-Throughput Screening (HTS). Consequently, some researchers developed three improved photoproteins optimized for the generation of precise Ca2+ mobilization assays photina, i-photina and c-photina. Although the total light release of these photoproteins is greater and their reaction kinetic is slower compared to other existing photoproteins, opening new opportunities for the application of flash luminescence assays in HTS. Recently, the three photoproteins by several companies such as PerkinElmer and Axxam have been commercialized. So, we selected i-photina which has the highest luminescence signal and good stability compared with two other photoproteins. Materials and Methods : Codon usage of i-Photina was optimized for both E. coli and mammalian cells. The encoding gene of i-photina was synthesized and overexpressed in E. coli. Then i-Photina was characterized and compared with aequorin. Results: i-Photina showed about a 14-fold higher bioluminescence signal than aequorin. Ca2+ sensivity of i-Photina was found to be slightly less than aequorin. In respect to other measured properties such as degree of stability, bioluminescence spectrum and decay half-life time, these two photoproteins were almost the same. Conclusion: i-Photina is an improved version of photoprotein that in many ways is superior to use of other Ca2+ indicators for HTS assays and can also be considered as a potential candidate for creating genetic mutations improved the bioluminescence propertises.